Investigating Pervaporation for In Situ Acetone Removal as Process Intensification Tool in ω‐Transaminase Catalyzed Chiral Amine Synthesis. (31st October 2018) - Satyawali, Yamini; del Pozo, David Fernandes; Vandezande, Pieter; Nopens, Ingmar; Dejonghe, Winnie
Abstract : Hydrophobic pervaporation (PV), allowing for the separation of an organic component from an aqueous stream, was investigated for in situ acetone removal from a transamination reaction. A poly(dimethylsiloxane) membrane was applied in a coupled enzymatic process at 5 L scale. Among the four components, there was no loss of donor and product amines through PV which was highly desirable. However, in addition to removal of acetone, there was also an unwanted loss of acetophenone (substrate ketone) because of PV. The coupled enzyme‐PV process resulted in 13% more product formation compared to the control process (where no PV was applied) after 9 h. Results from a qualitative simulation study (based on partial vapor pressures and a vapor–liquid equilibrium of the feed solution) indicated that PV might have an advantage over direct distillation strategy for selective removal of acetone from the reaction medium. © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 35: e2731, 2019